Pemanfaatan Augmented Reality dalam Pembelajaran IPAS untuk Meningkatkan Minat Belajar Siswa Kelas IV Sekolah Dasar - Elma Ayu Pratama; Siti Aisyah; Syailin Nichla Choirin Attalina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to investigate the effectiveness of utilizing Augmented Reality (AR) technology in Science and Social Studies (IPAS) learning, specifically focusing on local wisdom material, to enhance the learning interest of fourth-grade students at SD 4 Srobyong. Conventional teaching methods often face challenges in fostering student enthusiasm for abstract or culturally specific material. AR, with its ability to integrate the real world with virtual elements interactively, offers significant potential to overcome these problems. The subjects of this study were fourth-grade students at SD 4 Srobyong. Data were collected through observation, a learning interest questionnaire, and interviews. The results indicate that the implementation of AR in IPAS learning, particularly for local wisdom topics, creates a more immersive and engaging learning experience, which significantly correlates with an increase in students' learning interest. It was found that students participated more actively in learning activities, demonstrated higher curiosity, and had a better understanding of concepts related to their local heritage.